2017
DOI: 10.2337/db17-1039
|View full text |Cite
|
Sign up to set email alerts
|

Defective Amplifying Pathway of β-Cell Secretory Response to Glucose in Type 2 Diabetes: Integrated Modeling of In Vitro and In Vivo Evidence

Abstract: In vivo studies have investigated the role of β-cell dysfunction in type 2 diabetes (T2D), whereas in vitro research on islets has elucidated key mechanisms that control the insulin secretion rate. However, the relevance of the cellular mechanisms identified in vitro (i.e., the triggering and amplifying pathways) has not been established in vivo. Furthermore, the mechanisms underpinning β-cell dysfunction in T2D remain undetermined. We propose a unifying explanation of several characteristic features of insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
(62 reference statements)
4
24
0
Order By: Relevance
“…It has been reported that impairment of amplifying pathways could be one of the major causes underlying the beta cells dysfunction in T2D . In 2006 our research group observed the absence of amplifying pathways in islets from MSG‐obese rats, which was also found in the present study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It has been reported that impairment of amplifying pathways could be one of the major causes underlying the beta cells dysfunction in T2D . In 2006 our research group observed the absence of amplifying pathways in islets from MSG‐obese rats, which was also found in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Our data show that chronic exercise training reduces GSIS by inhibiting amplifying pathways in pancreatic islets; an effect that was more evident in islets from MSG‐EXE rats. To date, the accurate molecular and biochemical mechanisms involved in amplifying pathways and how these events are coupled to the exocytosis of insulin granules are still unclear . Interestingly, cholinergic effects on beta cells are also considered to be amplifying pathways .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these indices we calculated the Disposition Index (Matsuda ISI x InsAUC30/GluAUC30) which is a measure of beta-cell function adjusted for prevailing insulin sensitivity, and suitable for large population-based studies. Mathematical modeling to determine beta-cell function need multiple measurements in an OGTT, and is not feasible for large scale population-based studies [82], [83].…”
Section: Future Of the Biomarker Studiesmentioning
confidence: 99%
“…In addition to the ATP‐dependent depolarization, action potential firing, and increases in intracellular Ca 2+ stimulated by glucose (collectively called the ‘triggering’ pathway), a secondary pathway which may be mediated by multiple possible metabolic signals (Prentki, Matschinsky, and Madiraju, 2013) acts to facilitate exocytotic responses to the increased Ca 2+ . In fact, these ‘metabolic amplification’ pathways may act early to set the amplitude of glucose‐induced secretory responses – and reduced efficacy of this pathway may contribute to impaired insulin secretion in type 2 diabetes (T2D) (Grespan et al, 2018). One important pathway that contributes to the metabolic amplification of insulin secretion links the mitochondrial export of (iso)citrate and cytosolic generation of NADPH (Joseph et al, 2006; Ronnebaum et al, 2006) which facilitates insulin exocytosis (Ivarsson et al, 2005; Reinbothe et al, 2009) via the deSUMOylating enzyme sentrin‐specific protease‐1 (SENP1) (Ferdaoussi et al, 2015) acting on proteins at the exocytotic site (Dai et al, 2011; Ferdaoussi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%